Determinants of food delivery platforms through customer loyalty toward sustainability of business - Goh, Se Yeen; Lau, Xue Ni; Ong, Mei Jeat; Tan, Hong Wei; Tiew, Ming Lun (2020)
Food Delivery Service is one of on demand service where is provide convenience and profitability toward consumers, business owner and food delivery service platform. It also provides additional safety toward public in current COVID 19 pandemic. Customer can now obtain food & beverage in a much easier and convenience way with the help of food delivery platform. F ood and B everage business owner can also increase its customer base, popul arity by joining various food delivery platform. As an on growing delivery service industry in Malaysia, it is beneficial toward food & beverage business and mass public to understand the reason behind its growth and drawbacks. This research is set to exam ine the relationship among Trust in Internet, Convenience, Website Quality, Website Content, Perceived Value and Customer Loyalty (mediator) towards Sustainability of Business. 392 respondents live in 3 targeted area with food delivery service experience w ere selected as target subject in this research. All variables were chosen to show a positive relationship through mediator towards susta inability of business. Convenience, Website Content, Perceived Value are proven to be statistic significant towards Sus tainability of Business; while Trust in Internet, Website Quality are proven to be statistic insignificant towards Sustainability of Business. User friendly and sufficient information will lead to food delivery software increase its user bases; while suffi cient and informative content, reasonable price will lead to food & beverage business have more reach to consumer.